Stability of Individual Maillard Reaction Products in the Presence of the Human Colonic Microbiota - Hellwig, Michael; Bunzel, Diana; Huch, Melanie; Franz, Charles M. A. P; Kulling, Sabine E; Henle, Thomas (Journal of agricultural and food chemistry, 2015)
Maillard reaction products (MRPs) are taken up in substantial amounts with the daily diet, but the majority are not transported across the intestinal epithelium. The aim of this study was to obtain first insights into the stability of dietary MRPs in the presence of the intestinal microbiota. Four individual MRPs, namely, N-ε-fructosyllysine (FL), N-ε-carboxymethyllysine (CML), pyrraline (PYR), and maltosine (MAL), were anaerobically incubated with fecal suspensions from eight human volunteers at 37 °C for up to 72 h. The stability of the MRPs was measured by HPLC with UV and MS/MS detections. The Amadori product FL could no longer be detected after 4 h of incubation. Marked interindividual differences were observed for CML metabolism: Depending on the individual, at least 40.7 ± 1.5% of CML was degraded after 24 h of incubation, and the subjects could thus be tentatively grouped into fast and slow metabolizers of this compound. PYR was degraded by 20.3 ± 4.4% during 24 h by all subjects. The concentration of MAL was not significantly lowered in the presence of fecal suspensions. In no case could metabolites be identified and quantified by different mass spectrometric techniques. This is the first study showing that the human colonic microbiota is able to degrade selected glycated amino acids and possibly use them as a source of energy, carbon, and/or nitrogen.